Patient-specific FDG dosimetry for adult males, adult females, and very low birth weight infants - Niven, Erin (My University, 2003)
Fluorodeoxyglucose is the most commonly used radiopharmaceutical in Positron Emission Tomography, with applications in neurology, cardiology, and oncology. Despite its routine use worldwide, the radiation absorbed dose estimates from FDG have been based primarily on data obtained from two dogs studied in 1977 and 11 adults (most likely males) studied in 1982. In addition, the dose estimates calculated for FDG have been centered on the adult male, with little or no mention of variations in the dose estimates due to sex, age, height, weight, nationality, diet, or pathological condition.
Through an extensive investigation into the Medical Internal Radiation Dose schema for calculating absorbed doses, I have developed a simple patient-specific equation; this equation incorporates the parameters necessary for alterations to the mathematical values of the human model to produce an estimate more representative of the individual under consideration. I have used this method to determine the range of absorbed doses to FDG from the collection of a large quantity of biological data obtained in adult males, adult females, and very low birth weight infants. Therefore, a more accurate quantification of the dose to humans from FDG has been completed. My results show that per unit administered activity, the absorbed dose from FDG is higher for infants compared to adults, and the dose for adult women is higher than for adult men. Given an injected activity of approximately 3.7 MBq kg -1 , the doses for adult men, adult women, and full-term newborns would be on the order of 5.5, 7.1, and 2.8 mSv, respectively. These absorbed doses are comparable to the doses received from other nuclear medicine procedures.